PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI BADAN USAHA MILIK DESA (BUMDES) - Neneng Rini Ismawati (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2020)
Development and empowerment are things that are commonly discussed for the progress and change of the nation at this time. One of the efforts of the village government in overcoming the problem of poverty is the formation of Village-Owned Enterprises (BUMDES). This study aims: 1) to explain the social conditions of the people of Teluk Terate Village, 2) to explain how to empower the community's economy through BUMDES. 3) to explain how the results of community economic empowerment through BUMDES. In this study, I used descriptive qualitative research methods with field research. The results of this study indicate that the community feels helped by the existence of BUMDES Sabar Subur. 1) One of them is by sending a number of residents who are unemployed due to low education factors to the Manpower Services Unit, 2) Community economic empowerment through BUMDES runs well through the stages of awareness, training, mentoring and evaluation. And has several business units such as Sharia Microfinance Institution Business Unit (LKMS), Training and Employment Business Unit, Production and Trade Business Unit and Service and Rental Business Unit. 3) With the existence of this business unit, the people of Teluk Terate Village already have a business of cassava chips, catfish farms, and several quite large stalls. And seen from the inhibiting factors, it is hoped that the management of BUMDES can be even better with innovations and new BUMDES board members.